The Diamond brothers in... Public enemy number two - "Horowitz, Anthony" (Walker Books: London, 2015)
Framed for a jewel robbery, Nick Diamond finds himself sharing a prison cell with Johnny Powers, Public Enemy Number One. His only chance of escape is his older brother Tim, the world's worst private detective. But with Ma Powers and her gang waiting to greet the jailbirds, the heat is really on!
Keywords: Detective and mystery fiction